Niche breadth and range area in North American trees. Issue 3 (15th August 2012) - Morin, Xavier; Lechowicz, Martin J.
<x xml:space="preserve">Abstract</x> Identifying factors affecting species distribution is a longstanding goal in ecology and evolution that is accentuated by our need to anticipate climate change impacts. We sought to test whether any phylogenetic effect can be detected in either the environmental characteristics or range attributes of North American trees, and to explore the existence of a general interspecific pattern in the environmental factors influencing species range size. To do so we tested prevailing hypotheses relating climatic and edaphic characteristics to species range size in the North American arboflora (n = 598), using spatial null models to test for the relevance of observed patterns. We found that interspecific variation in the range area of North American trees is strongly related to the environmental regimes characteristic of the species range. Linear models and phylogenetic regressions involving six environmental characteristics explained 83% of the variance in species range area, and affirmed a positive relationship between niche breadth and range size. Tree species that can tolerate a larger variability in local climatic conditions, deal with harsher edaphic conditions, and weak levels of environmental energy tend to have larger range area; this can account for the greater geographic range of species at higher latitudes, the Rapoport effect. There is a significant phylogenetic signal for both range area and limits in North American trees, and for climatic limits, but not for energy or edaphic characteristics associated with species range. These findings highlight the possibility that species with small geographic ranges may be more sensitive to the effects of climate change.